Messianism as Religious Nationalism: Postcolonial Hermeneutics on Matthew 25:31–46 - Deky Nofa Aliyanto; Yusak B. Setyawan; Izak Y.M. Lattu; Suwarto Adi (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Messianism in the Judeo-Christian tradition is closely related to the collective experience of political subjugation and socio-economic marginalization, particularly under Roman rule after the Jewish–Roman War (66–70 CE). This study analyzes Matthew 25:31–46 within this context using a postcolonial hermeneutic approach, interpreting messianism as a form of religious nationalism. The study presents two main findings. First, the figure of the “Son of Man” represents a form of religious nationalism that functions as symbolic resistance to Roman imperial authority. Second, the identification of the Messiah with “the least of my brothers” reflects religious nationalism as a form of national solidarity rooted in the lived experience of the oppressed. This study contributes to postcolonial biblical interpretation by highlighting how the text constructs collective identity and resistance within a colonized community. It also offers implications for Matthean studies by reframing the passage beyond ethical and eschatological readings toward its ideological and socio-political dimensions.